Laterality and technical-tactical shot indicators in elite Water Polo - Argudo-Iturriaga, F. M.; Borges, P. (European Journal of Human Movement, 2025)
The aims of this study were to compare the effectiveness of left-handed vs. right-handed players in goal-related actions and positive technical-tactical outcomes during play and evaluate shot efficacy across field positions in elite Water Polo. A total of 5422 shots (2724 male - 2698 female) from the XXXIV Male European Water Polo Championships and XVIII Female European Water Polo Championships were analysed using a nomothetic, multidimensional observational design. Inter-observer reliability (kappa > 0.90) was confirmed. Statistical analyses were performed using SPSS 28.0, employing Mann-Whitney U or chi-square tests to compare categorical outcomes. Results revealed left-handed players demonstrated superior efficacy in zones 1 and 2 (45.5% vs. 22.2% in zone 1; 48.8% vs. 36.3% in zone 2, p < 0.05) and generated more positive actions (23.9% vs. 13.8%). Shots from zones 1 and 2 showed lower efficacy compared to central positions (p < 0.01). These findings suggest that coaches should strategically exploit the positional advantages of left-handed -particularly in lateral attacking zones - by designing offensive structures and training tasks. Moreover, understanding the reduced efficacy of peripheral shooting zones can help refine defensive planning and guide players toward higher-probability shooting positions.